Komitmen Organisasional : Peran Budaya Organisasional dan Kepemimpinan Transformasional (Studi Pada Karyawan PT Bukit Asam Tbk. Pelabuhan Tarahan Bandar Lampung - Chandra Saputra; Stefanus Rumangkit (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2021)
The purpose of this study was determine the effect of Organizational Culture, Transformational Leadership on the employee Commitment Organizational. The research method used in this study is a quantitative method through a survey with a population of 246 people with 114 samples. Human resource need to be managed properly so that the commitment of member organizations is high so that the level of human resource turnover will be low. Organizational commitment needs to be increased by providing support to members so that they have a perception that the organization has valued its contribution, leaders who are able to provide direction and motivation to members to do something better than they expected, and within the organization there must also be organizational cultures can be accepted by all members so that they can maintain members to remain highly committed to supporting the achievement of the goals of the organization.